Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a\)
\(\sqrt{7}+\sqrt{15}\)
\(=\sqrt{7+15}\)
\(=4,69\)
\(4,69< 7\)
\(\Rightarrow\sqrt{7}+\sqrt{15}< 7\)
\(b\)
\(\sqrt{7}+\sqrt{15}+1\)
\(=\sqrt{7+15}+1\)
\(=4,69+1\)
\(=5,69\)
\(\sqrt{45}\)
\(=6,7\)
\(5,69< 6,7\)
\(\Rightarrow\)\(\sqrt{7}+\sqrt{15}+1\)\(< \)\(\sqrt{45}\)
\(c\)
\(\frac{23-2\sqrt{19}}{3}\)
\(=\frac{22.4,53}{3}\)
\(=\frac{95,7}{3}\)
\(=31,9\)
\(\sqrt{27}\)
\(=5,19\)
\(31,9>5,19\)
\(\text{}\Rightarrow\text{}\text{}\)\(\frac{23-2\sqrt{19}}{3}\)\(>\sqrt{27}\)
\(d\)
\(\sqrt{3\sqrt{2}}\)
\(=\sqrt{3.1,41}\)
\(=\sqrt{4,23}\)
\(=2,05\)
\(\sqrt{2\sqrt{3}}\)
\(=\sqrt{2.1,73}\)
\(=\sqrt{3,46}\)
\(=1,86\)
\(2,05>1,86\)
\(\Rightarrow\sqrt{3\sqrt{2}}>\sqrt{2\sqrt{3}}\)
\(Học \) \(Tốt !!!\)
a) Ta có : \(\sqrt{7}< \sqrt{9}=3;\sqrt{15}< \sqrt{16}=4\)
Do đó : \(\sqrt{7}+\sqrt{15}< 3+4=7\)
b) Ta có : \(\sqrt{17}>\sqrt{16}=4;\sqrt{5}>\sqrt{4}=2\)
\(\Rightarrow\sqrt{17}+\sqrt{5}+1>4+2+1=7\)
Lại có : \(\sqrt{45}< \sqrt{49}< 7\)
Do đó : \(\sqrt{17}+\sqrt{5}+1>\sqrt{45}\)
c) Ta thấy : \(\sqrt{19}>\sqrt{16}=4\)
\(\Rightarrow2\sqrt{19}>2.4=8\)
\(\Rightarrow-2\sqrt{19}< -8\)
\(\Rightarrow23-2\sqrt{19}< 23-8=15\)
\(\Rightarrow\frac{23-2\sqrt{19}}{3}< 5\). Mặt khác : \(\sqrt{27}>\sqrt{25}=5\)
Nên : \(\frac{23-2\sqrt{19}}{3}< \sqrt{27}\)
d) Vì : \(18>12>0\Rightarrow\sqrt{18}>\sqrt{12}>0\)
\(\Leftrightarrow3\sqrt{2}>2\sqrt{3}>0\)
\(\Rightarrow\sqrt{3\sqrt{2}}>\sqrt{2\sqrt{3}}\)
a)\(\sqrt{8}+3< \sqrt{9}+3=3+3=6< 6+\sqrt{2}\)
b)\(14=\sqrt{196}>\sqrt{195}=\sqrt{13.15}=\sqrt{13}.\sqrt{15}\)
c) Ta có: \(\hept{\begin{cases}\sqrt{27}>\sqrt{25}=5\\\sqrt{6}>\sqrt{4}=2\end{cases}\Rightarrow\sqrt{27}+\sqrt{6}+1>5+2+1=8}\)
Mà \(\sqrt{48}< \sqrt{49}=7< 8\)
\(\Rightarrow\sqrt{27}+\sqrt{6}+1>\sqrt{48}\)
Tham khảo nhé~
a,\(\sqrt{12}=2\sqrt{3}=\sqrt{3}+\sqrt{3}\)
ta có \(\sqrt{5}>\sqrt{3}\)và\(\sqrt{7}>\sqrt{3}\)=>\(\sqrt{5}+\sqrt{7}>\sqrt{12}\)
\(\frac{23-2\sqrt{9}}{3}=\frac{23\sqrt{29.4}}{3}=\frac{23\sqrt{116}}{3}< \frac{23\sqrt{144}}{3}=\frac{23.12}{3}=92< 100=\sqrt{10}\)
Mà \(\sqrt{10}< \sqrt{27}\)nên \(\frac{23-2\sqrt{9}}{3}< \sqrt{27}\)
Vậy,...
\(a,x=\sqrt{27}-\sqrt{2}\)\(=3\sqrt{3}-\sqrt{2}>3\sqrt{3}-\sqrt{3}=2\sqrt{3}\)
Mà: \(y=\sqrt{3}< 2\sqrt{3}\)
\(\Rightarrow x>y\)
\(b,x=\sqrt{5\sqrt{6}}\Rightarrow x^4=5^2.6=150\)
\(y=\sqrt{6\sqrt{5}}\Rightarrow y^4=6^2.5=180\)
\(\Rightarrow x^4< y^4\Rightarrow x< y\left(x,y>0\right)\)
\(c,x=2m;y=m+2\)
Ta có: \(x-y=2m-\left(m+2\right)=m-2\)
Ta xét các trường hợp:
- Nếu \(m< 2\Rightarrow m-2< 0\Rightarrow x< y\)
- Nếu \(m=2\Rightarrow m-2=0\Rightarrow x=y\)
- Nếu \(m>2\Rightarrow m-2=0\Rightarrow x>y\)
Ta có
\(\sqrt{123-22\sqrt{2}}=11-\sqrt{2}\)
\(\sqrt[3]{77\sqrt{2}-115}=\sqrt{2}-5\)
\(\Rightarrow\sqrt{123-22\sqrt{2}}+\sqrt[3]{77\sqrt{2}-115}=11-\sqrt{2}+\sqrt{2}-5=6\)
b)\(\frac{\sqrt{27}}{\sqrt{12}}+\frac{1}{2}\)
\(=\frac{\sqrt{3}.\sqrt{9}}{\sqrt{3}.\sqrt{4}}+\frac{1}{2}\)
\(=\frac{\sqrt{9}}{\sqrt{4}}+\frac{1}{2}\)
\(=\frac{3}{2}+\frac{1}{2}\)
\(\frac{4}{2}=2\)
a) \(\sqrt{45}.\sqrt{15}.\sqrt{27}\)
\(=\left(\sqrt{15}\right)^2.\left(\sqrt{3}\right)^2.\sqrt{9}\)
\(=15.3.3\)
\(=135\)
a) \(\sqrt{45}\cdot\sqrt{15}\cdot\sqrt{27}=\sqrt{45\cdot15\cdot27}=135\)
b) \(\frac{\sqrt{17}}{\sqrt{12}}+\frac{1}{2}=\frac{\sqrt{51}}{6}+\frac{3}{6}=\frac{\sqrt{51}+3}{6}\)
c) \(\sqrt{\frac{1}{3}}:\sqrt{\frac{27}{50}}\cdot\sqrt{2}=\sqrt{\frac{1}{3}\cdot\frac{50}{27}\cdot2}=\frac{10}{9}\)
d) \(\sqrt{117^2-108^2}=\sqrt{\left(117-108\right)\left(117+108\right)}=\sqrt{9\cdot225}=45\)
\(108\sqrt[3]{22}>88\sqrt[3]{27}\)